KEMAMPUAN MENULIS PARAGRAF ARGUMENTASI OLEH SISWA KELAS X SMA ISLAM BAWARI PONTIANAK - Damsah, Novi Arnie; Sukamto, Sukamto; Syambasril, Syambasril (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractIn relation to this research is "How is the ability to write paragraphs of argumentation by students of grade X of Semester 2 of SMA Islam Bawari Pontianak Lesson Year 2016/2017?". The subproblems of this study are how the ability to write paragraphs of argument by the students of grade X SMA Islam Bawari Pontianak Lesson Year 2016/2017 viewed from the aspect of content, the aspects of unity (cohesion), and aspects ketuan (coherence).This research uses descriptive method with quantitative research form. The technique used with it, the researcher is interested to examine students' ability to write paragraphs of Argumentation. Common issues In taking samples is a random sample technique (random). Data collection technique is done by indirect communication technique. The data collection tool used, the written test. Based on the results of data analysis is known the ability to write paragraphs of argumentation by students of class X SMA Islam Bawari Pontianak academic year 2016/2017 seen from the aspect of content is the percentage of 59.4% with enough category, seen from the aspect of unity (cohesion) is the percentage of 56.3 % With enough category, seen from aspect kemuan (coherence) is the percentage of 90,63% with very good category, and seen from all aspect is the percentage equal to 65,98% with enough category. Keywords: Ability, writing, paragraphs of argument, paragraph content, unity                        (Cohesion), cohesion (coherence).